2009
DOI: 10.1007/s12272-009-1700-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluations of enoxacin carboxamide derivatives

Abstract: The present work deals with the synthesis of various enoxacin analogues via nucleophilic substitution of 3-carboxylic acid moiety of the drug by aromatic amines. The free carboxylic group was utilized in the formation of amides and the effect of functional group exchange on different biological activities of the parent was evaluated. The structure of these derivatives was established by various spectroscopic techniques and mass spectrometry. The derivatives were evaluated as antibacterial agents against a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The ester was subjected to nucleophilic attack by adding 3 mmole methanolic solutions of aromatic amines or hydrazine respectively with continuous stirring to generate corresponding carboxamides or carbohydrazides. The reaction was processed for about 2–3 hours till completion, indicated by TLC [23]. The caroboxylates were prepared by stirring the mixture of gatifloxacin (1 gm, 2.48 mmole) and methanolic solution of alcohol or phenol derivative (3 mmole) in acidic medium at 60°C under reflux (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ester was subjected to nucleophilic attack by adding 3 mmole methanolic solutions of aromatic amines or hydrazine respectively with continuous stirring to generate corresponding carboxamides or carbohydrazides. The reaction was processed for about 2–3 hours till completion, indicated by TLC [23]. The caroboxylates were prepared by stirring the mixture of gatifloxacin (1 gm, 2.48 mmole) and methanolic solution of alcohol or phenol derivative (3 mmole) in acidic medium at 60°C under reflux (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…After removal of the upper phase, neutrophils were collected and subjected to hypotonic lysis of RBC with sterile distilled water for one minute, and then washed twice with HBSS -- . Macrophages from mouse peritoneal cavity were obtained as described in our previous paper [23]. Cells were re-suspended in HBSS -- to give 1 × 10 6 /mL.…”
Section: Biological Studiesmentioning
confidence: 99%
“…These include the cyclopropyl group at the N-1 position, the 4-methylpiperazine at C-7, and an amino moiety at C-6 as it has been demonstrated that this moiety can replace the usual fluorine in terms of activity. 42,43 As C-3 substituents, we planned to introduce groups conferring either antibacterial activity (carboxylic acid 31 and carboxamide 44,45 ) or EPI activity (ethyl ester). 25,29 To avoid the enolization of the C-4 keto group, a methyl group was introduced at the C-3 position in some derivatives.…”
Section: Rationale Designmentioning
confidence: 99%
“…It is evident from literature that most of the research on quinolone is directed towards group modification of the C-7 basic group of the quinolone and the effect of substitution at C-3 position of quinolones has not been studied to a large extent to produce new agents with better antimicrobial profile. Accordingly to explore the potential of 3-carboxylic quinolone derivatives as anti Gram positive and Gram negative agents, we have recently reported some novel enoxacin (Saeed Arayne et al, 2009) , levofloxacin (Sultana et al, 2011) and ofloxacin (Arayne et al, 2012) carboxamide analogues by introducing new functionality at C-3 position. In continuation of our research program to establish the structure-activity relationships of 3-carboxylic quinolone derivatives, we here in report some novel enoxacin analogues which have been prepared by introducing new functionality at C-3.…”
Section: Introductionmentioning
confidence: 99%